Eventos pluviométricos extremos e inundações: impactos e percepção de riscos na sede do município de Maranguape, Ceará-Brasil - Abreu, Nair Júlia Andrade de (2019)
The present thesis aims to identify and analyze the occurrence of extreme rainfall events (accumulated in 24h) and the flood risks in the Maranguape district, also discussing the perception of these risks in the neighborhoods Preguiça and Novo Maranguape I. This issue is extremely worrying and pertinent, given that extreme rainfall events and associated flood impacts and risks often endanger the well-being and safety of Society. The development of this study took place through the following procedures: survey and literature review about the thematic and the chosen area; field work; procurement and production of cartographic material; establishment of the intensity classes of extreme events occurred in the area, based on the methodology of precipitation maximums; presentation and discussion of data obtained (from IPECE, IBGE, municipal civil defense, newspapers and scientific studies) regarding the characterization of the area, impacts and risks of recorded floods; elaboration and application of a questionnaire and discussion of the perception of these risks. Among the results, 50 extreme rainfall events were identified from 1985 to 2018, and some of these events contributed to the occurrence of significant flood impacts in several neighborhoods of the area. It stands out among these, the event registered by FUNCEME on March 30, 2009, which totaled 139.6 mm in 24 h and contributed to the triggering of floods that affected families from different neighborhoods. In the current context, different flood indicators have been verified that indicate the existence of risks associated with the occurrence of extreme rainfall events in different areas of Maranguape district: Novo Maranguape I, Preguiça, Novo Maranguape II, Outra Banda, Gavião, Santos Dumont, Coité and Tangueira. In all these neighborhoods, except Santos Dumont, impacts have already occurred. It was found that many surveyed residents realize these risks, especially those already affected by floods. However, few residents adopt or have taken preventive measures. Moreover, the actions of the public power have not been enough either.